Modelo explicativo para o transtorno de ansiedade generalizada : o papel da intolerância à incerteza, preocupação e regulação emocional - Leite, Michelle de Farias (2022)
This dissertation aimed to map relationships between generalized anxiety disorder (GAD), intolerance of uncertainty (IU), worry and emotional regulation (ER). Four studies were carried out. In the Study 1, it was performed a narrative review of the literature, with the objective of raising the main theoretical and empirical aspects of GAD. The results identified the conceptual evolution, epidemiology, and clinical aspects, in addition to the physical, psychological and social repercussions caused by GAD. This review also emphasized the explanatory models currently existing about de GAD and their respective contributions. The Study 2 consisted of a scope review on the association between GAD and ER. We sought to gather the findings from the literature and analyze bibliometric, methodological and content aspects of the articles. It was observed that strategies considered as maladaptive, such as emotional suppression, tend to be positively associated with the occurrence of GAD, and that ER had a mediation and moderation effect in the explanation of GAD. In Study 3, a confirmatory factor analysis and measurement invariance of the Intolerance of Uncertainty Scale (IUS-12) was conducted to assess psychometric properties and parameters of the instrument. The results attested that the IUS-12 has a bidimensional structure, satisfactory psychometric characteristics and is invariant according to gender, education level, and family income. Finally, in Study 4 an empirical investigation was performed to test an explanatory model for GAD, including II and worry as predictor variables, ER strategies and emotional dysregulation (ED) as mediating variables, and gender as confounding factor of this relationship. The sample was composed of 944 individuals from the general population. It was found that the final model had a satisfactory fit, indicating that the direct and indirect relationships established between the variables were significant. However, ER strategies did not present a mediation effect. Only ED showed a mediator effect between IU, worry, and GAD. The findings pointed out in this dissertation may contribute to a greater understanding of the mechanisms of GAD, in addition to helping mental health professionals to direct specific interventions. In short, we hope to elucidate the link between potential factors that lead to the development of GAD and increase its occurrence probability.